2012
DOI: 10.2147/vhrm.s29010
|View full text |Cite
|
Sign up to set email alerts
|

Patient considerations and clinical impact of cholesteryl ester transfer protein inhibitors in the management of dyslipidemia: focus on anacetrapib

Abstract: Cardiovascular disease (CVD) is responsible for significant morbidity and mortality within the United States and worldwide. Although targeting low-density lipoprotein cholesterol (LDL-C) in the prevention of CVD has been shown to be effective, evidence exists to indicate that significant cardiovascular (CV) risk remains in patients receiving 3-hydroxy-3-methylglutaryl-coenzyme A reductase inhibitors (statins) – a risk that may be correlated with low levels of high-density lipoprotein cholesterol (HDL-C). Among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 72 publications
0
7
0
Order By: Relevance
“…Since ANA is a stronger CETP inhibitor than DAL [9, 47], at first, we considered the possible involvement of CETP activity in ANA mediated inhibition of LDLR/PCSK9 expression. By transfection of specific siRNAs to knockdown CETP mRNA expression in HepG2 cells, we observed that ANA produced a similar inhibitory effect on LDLR mRNA expression in si-CETP transfected cells and cells transfected with a nonspecific siRNA control oligonucleotides, thereby suggesting that CETP activity is not required for the observed downregulation of LDLR and PCSK9.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since ANA is a stronger CETP inhibitor than DAL [9, 47], at first, we considered the possible involvement of CETP activity in ANA mediated inhibition of LDLR/PCSK9 expression. By transfection of specific siRNAs to knockdown CETP mRNA expression in HepG2 cells, we observed that ANA produced a similar inhibitory effect on LDLR mRNA expression in si-CETP transfected cells and cells transfected with a nonspecific siRNA control oligonucleotides, thereby suggesting that CETP activity is not required for the observed downregulation of LDLR and PCSK9.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, inhibition of CETP activity raises plasma HDL-C and lowers LDL-C, which favorably reduces both CVD risk factors simultaneously. Over the last decade, a great deal of efforts has been put into the development of CETP inhibitors as new therapy to raise HDL-C [69]. Thus far, four CETP inhibitors have been tested in human clinical studies including torcetrapib (TOR) [7] dalcetrapib (DAL) [1013], anacetrapib (ANA) [1417] and evacetrapib (EVA) [18].…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, the report on Dal-OUTCOMES 15 made no mention of any one of the six observational cohort studies listed in Table 1 , all of which were already in print. The same is true of an article investigating the harm caused by torcetrapib in ILLUMINATE 43 , and of several recent review articles 44 48 .…”
Section: Perspectivementioning
confidence: 84%
“…Based on these studies, the significant reduction in apoB level in the treatment groups compared to that in the placebo group was consistent with the effect of CW on blood cholesterol levels. In addition, changes in CETP were concentration-dependent on plasma VLDL levels, and it has been reported that when CETP was inhibited, HDL-C and LDL-C levels changed in a beneficial direction [36,37,38]. These results suggest that CW in the body inhibited the activity of CETP, leading to the inability of VLDL to convert to LDL and consequently to a reduction in the levels of apoB and LDL-C.…”
Section: Discussionmentioning
confidence: 98%